WOMEN’S POLITICAL ROLE IN ISLAMIC FUNDAMENTALISM (CASE STUDY OF HISBUTTAHRIR INDONESIA ) - Mujahidudin Mujahidudin (Sulesana, 2012)
This article examines HTI’s view on the role of women (Muslimah) in the public sphere. HTI encourages Muslimah to take part in promoting HTI’s agendas in terms of domestic and public level.Therefore, it is quite often that in many public demonstrations on street HTI employs women and children. However, the political participation of women in the public arena for disseminating HTI’s objectives, especially sounding its particular demands such as corruption, is not driven by a sense of gender awareness, but this merely relates to religion’s obligation to conduct dakwah.